Religiosidade popular na Passio Sanctorum Perpetuae et Felicitatis - Matos, Denilson da Silva (2022)
Recent research on Early Christianity favors an approach that points to intense processes of cultural interaction between the early Christians and the Greco-Roman culture of the Mediterranean. This new approach contrasts with the traditional reading of Early Christianity, a reading that suggests a relative exemption from syncretic processes with Greco-Roman culture, privileging concepts such as “sect”, among others. In this case, we propose to look at Early Christianity as a movement that is culturally established through discursive and practical interactions with its surroundings. Thus, in this research, based on the concepts of Magic and Popular Culture, we propose an analysis of popular religious practices present in the Passio Sanctorum Perpetuae et Felicitatis. We highlight reports that bring the practices of martyrs closer to the religious practices of subalterns, with emphasis on consolidated practices within the scope of the people's religion, namely, the consultation of dreams and oracles of different types, with the purpose of managing conflicts and the scarcity of resources, as well as the preparation of amulets. From a comparative study between the Passio Sanctorum Perpetuae et Felicitatis and documents from different semiotic regimes, such as: images, oracular dreams, visions of the beyond and magic manuals, we seek to attest to the proximity with popular practices present in the Greco-Roman world. The research also offers a translation and a commentary of the Passio Sanctorum Perpetuae et Felicitatis, from critical editions, into Portuguese.(AU)